(3QSGdI aj GdehGYXs
(3ChdgG (B:s
(3GdehYXI GdChdi jbhd YR hLd (B:(3YLHJ def Cjbf HGdehJ cja jaQM hYLHJ def Cjbf HGdMSGH cja jLeY s
(3BNQgG (B:s
(3bGd GdfHj Ydjg GdSdGe (B((3GdYde TLQI hGdYed aGcgJgG aEf de jcf dgG aGcgI aGdfGQ Chdi HgG(B) (3UOb QShd Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdKGefIs
(3hgj EMOi hKdGKjf ehYXIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdCRgQjI (B(8/33580) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs